Djibouti : 2007 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
Djibouti's 2007 Article IV Consultation focuses on the medium-term growth prospects and policies necessary to ensure that growth is broad based and accompanied by sufficient employment creation. Real GDP growth is estimated at 4.8 percent in 2006, driven by fiscal expansion, and a sizable private investment in the port and construction sectors. Consumer price inflation has increased slightly from 3.1 percent on average in 2005 to 3.6 percent in 2006, reflecting mainly increases in the prices of food, housing, water, and electricity.